2019
DOI: 10.1159/000499569
|View full text |Cite
|
Sign up to set email alerts
|

Nectin-1 Expression in Colorectal Cancer: Is There a Group of Patients with High Risk for Early Disease Recurrence?

Abstract: Background: Despite improvements in therapy of colorectal cancer, some patients will present occurrence of recurrence either locally or distantly. Tumor metastasis constitutes the major cause of cancer-associated morbidity and mortality. Nectin-1 belongs to the family of immunoglobulin-like cell adhesion molecules that contribute to the formation of cell-cell adhesions and regulate a series of cellular activities including cell polarization, differentiation, movement, proliferation, and survival. Expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Nectin1 is one of the four members of the Nectin family and is expressed in many cell types, including neurons, fibroblasts, and epithelial cells [ 27 ]. In the context of cancer research, one study reported that Nectin1 expression was associated with shorter progression-free survival of colorectal cancer patients [ 21 ]. Another study reported that Nectin1 expression in cancer-associated fibroblasts of pancreatic ductal adenocarcinoma was significantly related to invasion, metastasis, and shorter OS [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nectin1 is one of the four members of the Nectin family and is expressed in many cell types, including neurons, fibroblasts, and epithelial cells [ 27 ]. In the context of cancer research, one study reported that Nectin1 expression was associated with shorter progression-free survival of colorectal cancer patients [ 21 ]. Another study reported that Nectin1 expression in cancer-associated fibroblasts of pancreatic ductal adenocarcinoma was significantly related to invasion, metastasis, and shorter OS [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although limited number of studies have analyzed the role of Nectin1 in tumors, most of these studies have found that Nectin1 expression is associated with cancer progression. In colorectal cancer, Nectin1 expression was associated with a worse 3-year progression-free survival rate [ 21 ]. Furthermore, Nectin1 expression in cancer-associated fibroblasts was correlated with a poor prognosis in pancreatic ductal adenocarcinoma patients [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 111 clinically annotated surgically removed primary CRC samples was retrospectively identified from the database of patients of the 2nd Department of Propedeutic Surgery in Laiko General Hospital in Athens, Greece [25]. The specimens were collected from the established colorectal tumor tissue bank of the Institute of Pathology of the National and Kapodistian University, Athens Medical School, Laiko General Hospital.…”
Section: Patients and Tissues Specimensmentioning
confidence: 99%
“…Regarding lymph node metastasis, 53.2% of the patients had no lymph node metastasis, 21.6% presented lymph node metastasis in 1-3 regional lymph nodes, and 25.2% to 4 or more regional lymph nodes. Metastatic disease in terms of resectable liver metastasis was present in 15…”
Section: Baseline Descriptive and Tumor Characteristics Of The Study Populationmentioning
confidence: 99%